Circulating miR-221/222 reduces CD4+ T cells by inhibiting CD4 expression in colorectal cancer. (6th August 2021) - Hu, Jiajia; Zhang, Jiawei; Yu, Meng; Liu, Zukai; Zou, Yan; Hong, Liwen; Zhang, Tianyu; Sun, Jing; Zheng, Minhua; Zhu, Xuekai; Wang, Zhengting; Liu, Sanhong
Abstract: Many patients with cancers have low levels of CD4 + in their peripheral blood. However, the molecular mechanism is still unclear. Here, we found that the blood levels of miR-221 and miR-222 were dramatically increased in patients with colorectal cancer (CRC), and both circulating miR-211 and miR-222 served as sensitive diagnostic markers with an area under the curve of 0.8790 and 0.9148, respectively. Transfection of either miR-221 or miR-222 resulted in the reduction of the surface CD4 antigen level but not the surface CD8 antigen level. The luciferase reporter assay showed that miR-221/222 directly regulated CD4 expression in human primary T cells. These data showed that miR-221/222 levels were upregulated in the blood of patients with CRC and that the expression of CD4 in human primary T cells was inhibited by miR-221/222. These findings provide a novel strategy for modulating the number of CD4 + T cells in the blood and further adjusting the microenvironment suitable for immunotherapy.